Assessment of the Diversity of Endophytic, Rhizospheric and Soil Bacteria Using a Targeted Metagenomic Approach in Mali - (:unkn) unknown (My University, 2024)
Aims: This study investigates the diversity of endophytic, rhizospheric, and soil bacterial species in agricultural ecosystems in Mali using a targeted metagenomic approach based on 16S rRNA sequencing. The primary aim is to characterize microbial communities and understand their potential roles in enhancing agricultural productivity and sustainability in Mali's unique environmental conditions. Study Design: The study involved several key steps to ensure rigorous data acquisition and analysis. First, the raw sequence files (ab1 format) were converted into FASTA format, followed by the concatenation of sequenced fragments with both sense and antisense primers. Next, forward and reverse sequences were aligned, and a consensus sequence was generated for each sample. The sequences were then compared using the BLAST algorithm to identify bacterial species, and phylogenetic analysis was performed to assess evolutionary relationships and microbial diversity across samples. Location and Duration of the Study: The research was carried out at the African Center of Excellence in Bioinformatics and LaboREM-Biotech, Faculty of Sciences and Techniques, Bamako, Mali, from [insert time frame of study]. Methodology: Bacterial strains were selected from the microbial collection at LaboREM-Biotech. 16S rRNA sequencing was performed using the Sanger sequencing method. Data were processed and analyzed using a combination of bioinformatic tools, including sequence alignment, BLAST for species identification, and phylogenetic tree construction using relevant software. This methodology allowed for the precise identification of bacterial species and provided insights into the diversity of microbial communities in agricultural soils, rhizospheres, and plant roots. Results: A total of 35 bacterial species were identified, representing four major phyla and six bacterial classes. Among these, Bacillus emerged as the most predominant genus. Detailed phylogenetic analysis highlighte
Keywords: African Research